Assessing Energy Efficiency in Isp and Web Search Engine Collaboration - Rosas-Olivos, E; Hidalgo-Castillo, N (IEEE Computer Society, 2014)
Web Search Engines (WSE) are devised to cope with highly dynamic and demanding query rates. Reaction of users to worldwide events produces high peaks in traffic which forces data centers to have over-provisioned resources to support flash crowds events, however, most of the time servers have a low utilization wasting energy resources. In this paper we analyze the collaboration of the Internet Service Providers (ISPs), the WSE and end-home users. Our goal is to conclude about the possibility of this global model to decrease the energy consumption of data centers. The end-home users cooperate sharing energy resources to support overall query processing by being part of a distributed query results cache. Usually these resources are kept idling at homes most of the time so the question is whether these resources can be productively re-used and benefit the involved parties. The distributed cache allows ISP to reduce traffic outside its network and an energy reduction due to less over provisioning on the WSE side as bursty queries are now quickly cached inside the ISP. The caching strategy is based on managed peer boxes located at the edge of the network that significantly reduces peaks in traffic towards the WSE. Simulation results show an important potential for energy saving from the reuse of already committed baseline power of the managed boxes and the reduction of energy consumed by the WSE data center in case of proper collaboration involving the result freshness. © 2014 IEEE.